2011
DOI: 10.1111/j.1095-8649.2011.03117.x
|View full text |Cite
|
Sign up to set email alerts
|

Feeding strategy and cannibalism of the Argentine hake Merluccius hubbsi

Abstract: The diet composition and feeding strategy of the Argentine hake Merluccius hubbsi in the San Matías Gulf were analysed in order to use this information for the sustainable management of the fishery. Merluccius hubbsi behaved as an opportunistic predator. Small M. hubbsi consumed planktonic crustaceans, whereas medium and large fish ate numerous prey taxa with low frequency of occurrence and variable specific abundance. Intra- and intercohort cannibalism were detected in all size groups and were particularly si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 39 publications
2
17
1
Order By: Relevance
“…and the other two pelagic predator species (Macruronus magellanicus and Thyrsites atun) is also noteworthy. This observation fits well with modern observations in that M. magellanicus is a staple in the diet of Merluccius sp., as well as the cannibalistic habits identified in the latter species (Ocampo Reinaldo et al, 2011).…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…and the other two pelagic predator species (Macruronus magellanicus and Thyrsites atun) is also noteworthy. This observation fits well with modern observations in that M. magellanicus is a staple in the diet of Merluccius sp., as well as the cannibalistic habits identified in the latter species (Ocampo Reinaldo et al, 2011).…”
Section: Resultsmentioning
confidence: 87%
“…Modern δ 15 N values of muscle have shown that the Argentine hake (Merluccius hubbsi) and Southern hake (Merluccius australis) have a higher trophic level position than the Patagonian grenadier (Ciancio et al, 2008), as the former species characterized as consumers of intermediate size fish and squid and the latter as a macrozooplankton feeder. Cannibalism identified in the Argentina hake (Ocampo Reinaldo et al, 2011) could also explain the difference in trophic levels. No significant difference in δ 13 C values of muscle was observed between those species (Ciancio et al, 2008).…”
Section: Modern Samples and Reference Valuesmentioning
confidence: 97%
“…(). This is contrary to the results of other authors, who reported that the highest levels of cannibalism were found in larger individuals (Roel & MacPherson, ; Carpentieri et al ., ; Mahe et al ., ; Ocampo Reinaldo et al ., ; Link et al ., ). The recruits and spawners depth pattern found in the study area implies a spatial segregation and could be the main reason for the virtual absence of cannibalism in large specimens.…”
Section: Discussionmentioning
confidence: 98%
“…Owing to Argentine hake's commercial importance in the South Atlantic Ocean, its high abundance and the fact that it is an important predator in the Patagonian shelf waters (Laptikhovsky & Fetisov, ), many studies have examined its diet composition (Angelescu & Cousseau, ; Angelescu, Gneri, & Nani, ; Angelescu & Prenski, ; Belleggia, Figueroa, Irusta, & Bremec, ; Cordo, ; Ocampo Reinaldo, González, & Romero, ; Ruiz & Fondacaro, ; Sánchez, ; Sánchez & García De La Rosa, ; Sánchez & Prenski, ; Temperoni, Viñas, & Buratti, ). Although the feeding habits of Argentine hake have been studied in detail, there is no work analysing long‐term variations in diet composition.…”
Section: Introductionmentioning
confidence: 99%